Symptomatic intracerebral hemorrhage after non-emergency percutaneous coronary intervention: Incidence, risk factors, and association with cardiovascular outcomes - Lim, Mervyn Jun Rui; Zheng, Yilong; Soh, Rodney Yu-Hang; Foo, Qi Xuan Joel; Djohan, Andie Hartanto; Nga Diong Weng, Vincent; Ho, Jamie Sin-Ying; Yeo, Tseng Tsai; Sim, Hui-Wen; Yeo, Tiong-Cheng; Tan, Huay-Cheem; Chan, Mark Yan-Yee; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective To investigate the incidence, risk factors, and association with cardiovascular outcomes of patients who developed symptomatic intracerebral hemorrhage (ICH) after non-emergency percutaneous coronary intervention (PCI). Methods We conducted a single-institution retrospective study of patients who developed symptomatic ICH after non-emergency PCI. To identify associations between clinical variables and outcomes, Cox-proportional hazards regression models were constructed. Outcomes analyzed include (1) all-cause mortality, (2) acute ischemic stroke (AIS) or transient ischemic attack (TIA), and (3) major adverse cardiovascular events (MACE). Results A total of 1,732 patients were included in the analysis. The mean (±SD) age was 61.1 (±11.3) years, and 1,396 patients (80.6%) were male. The cumulative incidence of symptomatic ICH after non-emergency PCI was 1.3% (22 patients). Age, chronic kidney disease, and prior coronary artery bypass graft surgery were independently associated with a higher risk of ICH after PCI, while hyperlipidemia was independently associated with a lower risk of ICH after PCI. ICH after PCI was independently associated with a higher risk of all-cause mortality and AIS or TIA after PCI. Conclusion Patients who are older, who have chronic kidney disease, and who have had prior coronary artery bypass graft surgery should be monitored for symptomatic ICH after non-emergency PCI.